2014
DOI: 10.3748/wjg.v20.i20.6226
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cytokine gene polymorphisms and chronic hepatitis B virus infection

Abstract: Hepatitis B virus (HBV) infection is still a public health problem worldwide, being endemic in some parts of the world. It can lead to serious liver diseases such as chronic hepatitis, cirrhosis, and hepatocellular cancer. The differences in host immune response can be one of the reasons for the various clinical presentations of HBV infection. Polymorphisms of genes encoding the proinflammatory and antiinflammatory cytokines, which are responsible for regulation of the immune response, can affect the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 86 publications
1
40
1
Order By: Relevance
“…In conclusion, this study indicated that cytokine production was significantly influenced by the genotype frequency distribution. A possible positive relationship between serum IL-18 level and disease severity of HBV infection has been reported during a clinical study [19]. Another study conducted on a Chinese population, the IL-18 -137 SNP with C allele was shown to be associated with protection against HBV infection [20].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, this study indicated that cytokine production was significantly influenced by the genotype frequency distribution. A possible positive relationship between serum IL-18 level and disease severity of HBV infection has been reported during a clinical study [19]. Another study conducted on a Chinese population, the IL-18 -137 SNP with C allele was shown to be associated with protection against HBV infection [20].…”
Section: Discussionmentioning
confidence: 99%
“…While we cannot exclude that responses in severe subjects may result from WNV infection or effects of persistent antigen (17,48), our findings of differential innate cell function suggest that naive responses are being examined. Finally, it will be valuable to examine IL-1 responses across different populations, as IL-1 is known to vary in genetic association studies and, as a key regulator of the inflammatory process, may be critical to resistance to viral infections (49).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Tang et al (2014) carried out an investigation of 660 deep venous thrombosis patients and 660 control subjects, from which they found that the IL-10 -1082A/G polymorphism is associated with risk of this disease among Chinese individuals. Tunçbilek (2014) revealed that sequence variations in this same gene are involved in different clinical presentations of HBV infection, while Pan et al (2015) conducted a meta-analysis indicating that IL-10 -592A/C and -1082A/ G polymorphisms can affect susceptibility to sepsis. Ramis et al (2015) failed to identify a significant association between IL-10 gene variants and H. pylori infection; however, An et al (2015) reported that IL-10 -592A/C and -819C/T polymorphisms can influence valvular calcification risk in Han and Kazak populations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined associations between the IL-10 -592A/C, -819C/T, and -1082A/G polymorphisms and several conditions related to inflammation, including deep venous thrombosis, chronic hepatitis B virus infection, sepsis, Helicobacter pylori infection, valvular calcification, and peptic ulcer diseases (Tang et al, 2014;Tunçbilek, 2014;An et al, 2015;Miftahussurur and Yamaoka, 2015;Pan et al, 2015;Ramis et al, 2015). For instance, Tang et al (2014) carried out an investigation of 660 deep venous thrombosis patients and 660 control subjects, from which they found that the IL-10 -1082A/G polymorphism is associated with risk of this disease among Chinese individuals.…”
Section: Discussionmentioning
confidence: 99%